An Analysis of Sheikh Aḥmad Dīdāt’s Methodology of Argument in His Literature - Naqeeb Ullah; Ahmed, Sajjad (Journal of Islamic and Religious Studies, 2021)
Sheikh Aḥmad Dīdāt, the awardee of King Faisal award in 1986, was a enthusiastic, self-educated Muslim preacher from South Africa, most prominent for engaging Christian missionaries in open debates. Although he was famous for his sharp and impassioned debating style, he also published more than 20 books and wrote numerous articles and pamphlets, many of them were translated into different languages. He settled a specific discourse on the nature of relations between Muslims and followers of other religions through dialogues, public debates and written literature. This research aims to identify Dīdāt’s approaches in his literature, the impact of his methodolgy on Islamic-Christian dialogue, the methods used by him in this regard and the guidelines from his approches to improve Islamic-Christian dialogue in future. The study concludes that dialogue is one of the basic means to achieve peace and peaceful coexistence in the modern era. Moreover, Dīdāt adheres to the original and authentic sources of the Christians, and promotes the calm dialogue based on the principles of sober scientific research, in order to achieve security and peaceful coexistence. The researchers recommend establishment of an active international Islamic body for dialogue, far from political influences and directives, to prepare scientific and intellectual cadres of Muslim interlocutors at all levels.